2013
DOI: 10.3748/wjg.v19.i26.4185
|View full text |Cite
|
Sign up to set email alerts
|

Cap polyposis: A rare cause of rectal bleeding in children

Abstract: Cap polyposis is a rare and under-recognised cause of rectal bleeding in children. Our study has characterized the disease phenotype and treatment outcomes in a pediatric cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 18 publications
2
30
1
Order By: Relevance
“…Additionally, our patient presented with rectal bleeding, mucoid discharge, abdominal pain, and a fiveyear history of straining during defecation, progressing in severity over time. Although anemia, changes in serum inflammatory markers, and a decrease in total serum protein or albumin levels have been reported in some cases [4], our patient had no laboratory abnormalities. Almost all lesions found during colonoscopy evaluation of adults or children are located in the rectum, occasionally extending to the anal canal, and less frequently in the sigmoid colon [2].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Additionally, our patient presented with rectal bleeding, mucoid discharge, abdominal pain, and a fiveyear history of straining during defecation, progressing in severity over time. Although anemia, changes in serum inflammatory markers, and a decrease in total serum protein or albumin levels have been reported in some cases [4], our patient had no laboratory abnormalities. Almost all lesions found during colonoscopy evaluation of adults or children are located in the rectum, occasionally extending to the anal canal, and less frequently in the sigmoid colon [2].…”
Section: Discussioncontrasting
confidence: 54%
“…Structure of a polypoid with an ulcerated granulation tissue cap and inflammatory exudates on the surface Fig. 4 At a higher magnification, granulation tissue is visible overlying tortuous crypts with basally located nuclei, as well as the presence of smooth muscle fibers and congested vessels in the inflamed stroma diseases such as IBD and mucosal prolapse syndrome, which results in frequent misdiagnosis and unnecessary or harmful evaluations or therapeutic strategies [2,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No distinct polyps could be found. Generally, cap polyps manifest as polypoid lesions with intervening normal mucosa[ 6 , 8 ]. However, contiguous polyps have been described and it is not uncommon that CP is often misinterpreted as chronic inflammatory bowel disease[ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case series showed that patients' median age was 52 years and the age range was from 12 years to 76 years (2). Li et al (3) reported the youngest case of cap polyposis in a 5-year-old male in 2013. The most common site of polyposis is the rectosigmoid colon, but lesions have also been detected proximal to the colon and in the stomach (4).…”
Section: Introductionmentioning
confidence: 99%